2020
DOI: 10.3390/pharmacy8040219
|View full text |Cite
|
Sign up to set email alerts
|

Potentially Inappropriate Medication Use in Older Hospitalized Patients with Type 2 Diabetes: A Cross-Sectional Study

Abstract: Background: Older patients with type 2 diabetes mellitus (T2DM) are at greater risk of receiving potentially inappropriate medications (PIM) during hospitalization which may result in adverse outcomes. Aim: To evaluate the extent of PIM use in the older population with T2DM during hospitalization in a tertiary care hospital in India. Methods: A cross-sectional study was carried out from August 2019 to January 2020 in a tertiary care teaching hospital among the older population (aged ≥ 65 years) hospitalized wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 33 publications
3
23
0
1
Order By: Relevance
“…Consistent with research at home and abroad, female patients had a higher risk of PIMs than male patients and was not restricted by the updated version of the Beers criteria. 21,37,38 The number of drugs was associated with the high detection rate of PIM prescriptions, which was similar to the results reported by other scholars. 39,40 Compared with patients with 1 to 4 drugs, patients with 5 to 9 drugs had more than 3 times the risk of PIMs, and patients with 10 or more drugs had at least 13 times the risk of PIMs.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Consistent with research at home and abroad, female patients had a higher risk of PIMs than male patients and was not restricted by the updated version of the Beers criteria. 21,37,38 The number of drugs was associated with the high detection rate of PIM prescriptions, which was similar to the results reported by other scholars. 39,40 Compared with patients with 1 to 4 drugs, patients with 5 to 9 drugs had more than 3 times the risk of PIMs, and patients with 10 or more drugs had at least 13 times the risk of PIMs.…”
Section: Discussionsupporting
confidence: 88%
“…According to the results of factor analysis, patients with female, aged ≥75 years, and combined medications ≥5 were more likely to receive PIMs when prescribed. Consistent with research at home and abroad, female patients had a higher risk of PIMs than male patients and was not restricted by the updated version of the Beers criteria 21,37,38 . The number of drugs was associated with the high detection rate of PIM prescriptions, which was similar to the results reported by other scholars 39,40 .…”
Section: Discussionsupporting
confidence: 83%
“…However, the current estimates of the prevalence of PIM use using the 2019 AGS Beers criteria were generally higher than those reported by previously published studies in Ethiopia using 2015 STOPP/START criteria and 2012 Beers criteria, reporting inappropriate medication use in 23% to 45% of the participants [ 20 , 31 ]. In addition, international studies using the 2019 AGS Beers criteria reported a high prevalence of PIM use in patients with heart failure in Lebanon (80%) [ 32 ], outpatients in Qatar (76%) [ 33 ], and patients with diabetes in India (74%) [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common classes of PIMs in our study were cardiovascular medications (27.8%), followed by endocrine agents (13.5%). In contrast, 84.2% of the PIMs were gastrointestinal medications in a Qatar study [ 33 ], and 44.6% were endocrine agents in India [ 34 ]. Other studies have reported different classes of PIMs, such as benzodiazepines [ 35 ], antidepressants and antipsychotics [ 36 ], and non-steroidal anti-inflammatory drugs [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Glimepiride is frequently observed as a PIM in older diabetes inpatients. 48 Initial treatment with sulfonylurea monotherapy increased ischemic stroke, cardiovascular death and all-cause mortality. 49 As it is cost-effective and has good glucose lowering potency, glimepiride remains competitive.…”
Section: Discussionmentioning
confidence: 99%